Experiences Of Pregnant Women In Consuming Multiple Micronutrient Supplements (Mms) In Caile Public Health Center, Bulukumba - Fitriani Fitriani; Tenriwati Tenriwati; Asdinar Asdinar (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2026)
Anemia remains a major public health problem among pregnant women and contributes significantly to maternal and fetal morbidity. Multiple Micronutrient Supplementation (MMS) has been introduced as an alternative to improve maternal nutritional status; however, adherence is influenced by individual experiences. This study aimed to explore the experiences of pregnant women in consuming MMS in the working area of Caile Public Health Center, Bulukumba. This study used a qualitative design with a phenomenological approach. Data were collected through in-depth interviews with eight pregnant women experiencing mild to moderate anemia. Data were analyzed using thematic analysis. The findings revealed three main themes: (1) perception of MMS, including understanding, information sources, and initial experiences; (2) impact of MMS consumption, including side effects and coping strategies; and (3) social support and cultural factors influencing adherence. Most participants perceived MMS as beneficial but experienced side effects such as nausea, dizziness, and gastrointestinal discomfort, which affected adherence. Family and healthcare provider support played a significant role in encouraging continued consumption, while cultural beliefs sometimes hindered adherence. In conclusion, adherence to MMS is influenced by a combination of perception, physiological response, and social-cultural factors. Strengthening education and support systems is essential to improve compliance among pregnant women.